Doenças hereditárias e defeitos congênitos em búfalos (Bubalus bubalis) no Brasil - Damé, Maria Cecília Florisbal (2013)
This thesis is a continuation of a research project started with a diagnosis of dermatosis mechano-bullosa in a herd of buffaloes from a farm in southern Rio Grande do Sul. After this diagnostic it was created an experimental herd where several congenital defects and / or hereditary disorders have been diagnosed during more than two decades. These diseases were studied by a research group which the author of this thesis is a member. Thus, three papers are presented: the first one is a literature review about what has been diagnosed in Brazil on congenital defects and hereditary diseases in buffalo. It was concluded that undesirable genes are widespread in the population of buffaloes in the country; the second was a study conducted in partnership with UNESP / Jaboticabal, SP and UFCG / CSTR-Patos, PB to identify the mutation in the gene that determines the oculo-cutaneous albinism in Murrah buffalo. Another paper was accomplished to describe the occurrence of malignant melanoma in two albino buffalo. Although it is not a congenital or hereditary disease it was observed only in the buffalo with oculocutaneous albinism and probably the condition is associated with a predisposition of these animals to develop tumors in the skin.